The Effect of Using the Virtual Classroom on the Achievement of the Eighth Grade Students in General Science Subject in Jordan - Ahmed, Dr. Fadi A.O. Bani (Opción)
The primary purpose of this study was to investigate the Effect of Using the Virtual Classroom on the Achievement of the Eighth Grade Students in General Science Subject in Jordan. The sample of the study consisted of 60 students divided into two equal groups. The control group consisted of (30) students and the experimental group consisted of (30) students too. The results of the study indicated that the level of achievement of students in the experimental group was higher than the students in the control group.